Analysis Of The Level Of Community Satisfaction With Health Services At The Temayang Health Center Bojonegoro District - Maulaningrum, Pristiya; Siti Mujanah; Alif Fianto, Achmad Yanu (PT Inovasi Pratama Internasional, 2025)
Quality health services are an important element in supporting public health status. This study aimed to analyze the level of community satisfaction with health services at Puskesmas Temayang and Bojonegoro Regency. The research method used was descriptive quantitative with 218 respondents selected through stratified random sampling. Data were collected through a standardized questionnaire based on Permenpan-RB Number 14 of 2017, with nine elements of the Community Satisfaction Survey indicator. The results showed that the Community Satisfaction Index (IKM) was in the good category. The dimensions of cost/tariff and complaint handling are at the highest value, while the facilities and infrastructure aspects have the lowest scores of other aspects. This shows that there is a need for improvement in physical facilities, both buildings, completeness of service support tools, and strengthening of the competence of health workers. This study is expected to be a strategic input for policymakers to improve the quality of health services, especially at the Puskesmas level.